Strategies and Challenges of Instagram-Based Digital Da'wah: Content Analysis on @nuruljadidmedia Accounts July-September 2024 - Agus Miftahorrahman; Kun Wazis; Siti Raudhatul Jannah; Indry Ayu Yuliana (Universitas Nurul Jadid, 2024)
This research discusses strategies and challenges in digital da'wah through the Instagram platform, with a focus on @nuruljadidmedia accounts. This research highlights the importance of da'wah as a command of Allah SWT and the challenges faced in conveying da'wah messages in the increasingly advanced digital era. The purpose of this study is to analyze the strategies implemented by the account and identify the challenges that arise in the context of digital da'wah. A descriptive qualitative approach with content analysis was used which included observations of da'wah content during the period from July to September 2024. Data is collected through upload documentation and systematic analysis of themes, categories, and important elements of content. The results showed that Instagram accounts @nuruljadidmedia used a persuasive communication approach both rationally and emotionally, with 74.55% of the total content analyzed applying the method. These findings indicate the effectiveness of using social media to attract young audiences and improve their understanding of Islamic teachings.